Analysis of the Effect of Number of Players on the Excitement of the Game with Respect to Fairness - Sagguneswaraan Thavamuni; Hadzariah Ismail; Hiroyuki Iida (Springer-Link, 2018)
Games can be played alone or with multiple people. We often assume that the game is more fun if played with someone, but we do not know much about how the number of players in a game affects the enjoyment of a fair game. From this research, we outlined that more players in a game increase the unpredictability of the game and its excitement overall. By applying the game refinement theory, we can see how the number of players can affect the excitement of a game. We also look at the pressure of a game on the players by utilizing the force-in-mind theory to further understand how games can motivate players without causing them too much stress.